Implementation of RME learning model supported by culture-based student worksheets in second-grade elementary schools to enhance mathematical understanding - Rahmah, Ananda Awaliyah; Isrok'atun, Isrok'atun; Irawati, Riana (Universitas PGRI Semarang, 2024)
This study aims to determine the effect of the RME model assisted by culture-based student worksheet on mathematical understanding of multiplication and division material in class II elementary schools. This type of research uses quantitative quasi-experiment with a pretest-posttest design. The research included class II students from select superior schools in the Rancakalong District, with two schools being chosen as samples for the study. In analyzing the data, assumption tests (normality and homogeneity), hypothesis testing and the N-Gain test were used. The instruments used were mathematical understanding tests as well as observation sheets of teacher performance and student activities. In this study, it was found that there was a positive influence of using the RME model assisted by culture-based student worksheet which resulted in an increase in N-Gain of 0.53 in the medium category. Then, based on the mean difference test carried out, it was concluded that there was a difference in the average of students' mathematical understanding in the RME model class assisted by culture-based student worksheet and the conventional model class with a better improvement in the experimental class.